A critical perspective on action research as a method for information systems research - Baskerville, Richard; Wood-Harper, A. (2016)
© Association for Information Technology Trust 2016.The purpose of this paper is to review critically the origins, techniques and roles associated with a growing information systems (IS) research method known as ‘action research’. This method is widely cited as an exemplar of a post-positivist social scientific research method, ideally suited to the study of technology in its human context. We seek to illuminate both the attractions and the detractions that this method holds for IS researchers.